Exploring lecturers' perspectives on enhancing student employability in English education: Curriculum, pedagogy, and departmental support - Hatmanto, Endro Dwi; Pratolo, Bambang Widi; Purwanti, Eko; Pasandalan , Sittie Noffaisah (Universitas Ahmad Dahlan, 2026)
While graduate employability has gained traction in higher education, its interpretation and operationalization in specific disciplines such as English Education have yet to be extensively examined. This study explored the lecturers’ perception of ways in which English Education Department can build the students’ employability through the curriculum, pedagogy and department support along with opportunities and challenges faced when embedding employability-oriented practices into the curriculum. This research used a qualitative design with multiple sites by interviewing ten lecturers of ten English Education Departments in Yogyakarta. Data were collected by conducting semi-structured interviews, which were then analyzed thematically. The results reveal that lecture staff see employability as something for the whole department to teach rather than an adjunct. The report highlights the need to diversify pathways through education, clarify and enhance the professional value of current learning activities, strengthen communication skills and soft skills cultivation, foster authentic and digitally mediated learning experiences, and invest in stronger external partnerships. But these efforts are limited by curriculum congestion, heterogeneous lecturer readiness, sparse institutional networks and tensions between labour-market pressures and disciplinary identity. The paper ends by arguing that in order to improve employability of English Education, coherent program-level co-ordination with sustained commitment at the department level is required.